2002
DOI: 10.1002/mds.10332
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic role of glial cells in Parkinson's disease

Abstract: Parkinson's disease (PD) is a common neurodegenerative disorder characterized by the progressive loss of the dopaminergic neurons in the substantia nigra pars compacta (SNpc). The loss of these neurons is associated with a glial response composed mainly of activated microglial cells and, to a lesser extent, of reactive astrocytes. This glial response may be the source of trophic factors and can protect against reactive oxygen species and glutamate. Alternatively, this glial response can also mediate a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
140
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(146 citation statements)
references
References 85 publications
6
140
0
Order By: Relevance
“…Several lines of evidence highlight the presence of activated glial cells expressing the proinflammatory cytokines IL-1b and TNF-a in the SN of PD patients (68) and MPTP-treated mice (69). IL-1b and TNF-a originating from activated glial cells may trigger intracellular death-related signaling pathways in the MPTP model of PD (70). This is comparable to our recent finding that activated microglia-derived IL-1b and TNF-a participated in DA neuronal death in an MPTP mouse model of PD (4).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence highlight the presence of activated glial cells expressing the proinflammatory cytokines IL-1b and TNF-a in the SN of PD patients (68) and MPTP-treated mice (69). IL-1b and TNF-a originating from activated glial cells may trigger intracellular death-related signaling pathways in the MPTP model of PD (70). This is comparable to our recent finding that activated microglia-derived IL-1b and TNF-a participated in DA neuronal death in an MPTP mouse model of PD (4).…”
Section: Discussionmentioning
confidence: 99%
“…One of the major mechanisms of cell death in dopaminergic neurons is believed to involve ROS (Cadet and Brannock, 1998), and dopamine itself can lead to the production of ROS through a number of processes (Teismann et al, 2003). There have been studies that suggest that GDNF can protect dopaminergic neurons against the toxic sequelae of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that Toll-like receptor 4 on microglial cells is involved in LPS-induced microglial activation in the present study. Other studies showed that various cytokines, reactive oxygen species, and nitric oxide are released by activated microglial cells (4,19,32). Accordingly, it is likely that these molecules also contribute to the LPS neurotoxicity on SN dopaminergic neurons.…”
mentioning
confidence: 97%
“…High concentrations of microglial cells are present in the SN, and activation of these cells has been observed in the SN of PD patients (1,2). Recent studies postulated that activation of microglia and neuroinflammatory processes may contribute to the pathogenesis of PD (3,4). Lipopolysaccharide (LPS), a component of the Gram-negative bacterial cell wall, is a potent inducer of inflammation and activator of microglia (5).…”
mentioning
confidence: 99%